2019
DOI: 10.52131/jom.2019.0101.0004
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Among Business Students and Its Impact On Academic Performance

Abstract: Purpose: Purpose of this research is to check the impact of Burnout among with Work Load and Stress on the Academic Performance of the university and thus then the ways to cope up with the burnout and then to get maximum academic performance. Design/Methodology/Approach: Total of 750 students were taken as population of this research and sample of 250 students were taken and distributed the questionnaire.  The responses were get back from 150 students to analyze through the SPSS. Findings: This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Taking many disciplines implies allocating more time to the course, increasing the volume of assignments, readings, and assessments (Carlotto, Nakamura and Câmara, 2006). This situation generates a sense of overload (Abacar, Aliante and Antonio, 2021;Batista and Castro, 2022) associated with BS (Carlotto, Nakamura and Câmara, 2006;Carlotto and Câmara, 2008;Ahmed and Shah, 2019). The result aligns with those obtained by Galdino et al (2020), who found that a higher discipline workload was associated with higher levels of all three dimensions of burnout in nursing students.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Taking many disciplines implies allocating more time to the course, increasing the volume of assignments, readings, and assessments (Carlotto, Nakamura and Câmara, 2006). This situation generates a sense of overload (Abacar, Aliante and Antonio, 2021;Batista and Castro, 2022) associated with BS (Carlotto, Nakamura and Câmara, 2006;Carlotto and Câmara, 2008;Ahmed and Shah, 2019). The result aligns with those obtained by Galdino et al (2020), who found that a higher discipline workload was associated with higher levels of all three dimensions of burnout in nursing students.…”
Section: Discussionsupporting
confidence: 77%
“…The stressor "having many disciplines to attend" has also been identified in other studies as a significant stressor in university students (Carlotto, Nakamura and Câmara, 2006;Carlotto and Câmara, 2008;Ahmed and Shah, 2019;Abacar, Aliante and Antonio, 2021;Batista and Castro, 2022). The arrangement of disciplines in the curriculum follows a pedagogical plan, however, it is also consistent with the expected duration of the course.…”
Section: Discussionmentioning
confidence: 59%